The impact of perceived value, customer expectations, and patient experience on the satisfaction of contracted patients in hospitals - Xin Rao; Li Luo; Jie Xiang; Xingyue Wang (BMC Health Services Research)
Abstract Background There is a growing focus on researching healthcare services to identify factors associated with satisfaction in family contract services in China. However, previous satisfaction studies have mainly focused on the primary healthcare. Currently, the primary healthcare service capacity in China is relatively insufficient, necessitating the involvement of upper-level hospitals in contracted services Thus, the study significantly deepens and broadens previous research on satisfaction in family contract services of hospital. Methods A conceptual model was developed and tested on a sample of customers and patients with hospital contract service (n = 624). Partial least-squares structural equation modelling (PLS-SEM) was used to analyse the data with SmartPLS4.0 software in two steps involving a measurement model and a structural model. Mediation analysis was used to test the proposed indirect effects. Results Contracted patient satisfaction is directly and positively associated with Perceived value (β = 0.223), Patient experience (β = 0.613) and Customer expectations (β = 0.129). The relationships between Customer expectations, Patient experience and contracted patient satisfaction are all mediated by Perceived value. Patient experience mediates the relationship between Customer expectations and contracted patient satisfaction. Overall, the proposed model explains 61.3% of the variance in customers and patients with hospital contract service’ satisfaction. Conclusions This study reveals a complex pattern of links between satisfaction and Customer expectations, Perceived value and Patient experience. However, the findings indicate that Customer expectations has an influential and multifaceted impact on satisfaction of customers and patients with hospital contract service satisfaction.